Davis and Gray Children at Medical School Groundbreaking - (:unkn) unknown (Coy C. Carpenter Library, 1940)
Published in 1944 Howler yearbook.
Egbert L. "Lawrence" Davis, III (left) and Bowman Gray, III (right) in 1940 playing with their groundbreaking shovels in the grass instead of in the dirt. The more famous and widely published photo of the two boys shows them actually turning dirt for the construction of the soon to be Bowman Gray School of Medicine.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth